Prospective clinical and manometric study comparing pneumatic dilatation and sublingual nifedipine in the treatment of oesophageal achalasia. Issue 6 (June 1991) - Coccia, G; Bortolotti, M; Michetti, P; Dodero, M
Abstract : A study was carried out in 30 patients affected by a mild or moderate degree of oesophageal achalasia to compare the clinical and manometric effects of sublingual nifedipine and pneumatic dilatation. Sixteen patients were dilated twice with Rider-Moeller dilators and 14 were treated with sublingual nifedipine 10-20 mg 30 minutes before meals. A manometric evaluation was performed before and six months after starting treatment. The clinical evaluation (according to Vantrappen's criteria) was performed every three months for a mean follow up of 21 months. In both groups of patients a significant (p less than 0.001) fall in lower oesophageal sphincter pressure was observed after treatment and excellent or good clinical results were observed in 75% of dilated patients and in 77% of patients treated with nifedipine. One patient could not tolerate nifedipine. No complications were observed after dilatation. It is concluded that longterm treatment with sublingual nifedipine and pneumatic dilatation are equally effective in the treatment of oesophageal achalasia of mild or moderate degree.